2021
DOI: 10.1108/md-01-2021-0117
|View full text |Cite
|
Sign up to set email alerts
|

Does market digitalization always benefit firms? The Latin American case

Abstract: PurposePrior research has found that firms' adoption of digital technologies (i.e. digitalization) enhances transaction efficiency and improves firm performance. However, this finding is based on the assumption that firms respond to consumers' adoption of digital technology (market digitalization) in a timely fashion. The study investigates the impact of market digitalization on firm performance in Latin America, where resistance to change is often higher, despite the positive impact on performance when compan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…In contrast, the lack of a systematic approach to relationship management may lessen the benefits of a strategic alliance outside the perimeter of the industrial group in the case of Company Alpha. Second, firms should avoid the adoption of fashionable digital solutions in favour of configurations that actually align with organisation sensemaking (Sanchez-Riofrio et al, 2021). Firm-specific approaches are needed to reflect the non-linear relationship between strategic planning and strategy deployment when digital technologies are involved (Li, 2020).…”
Section: Jmtm 349mentioning
confidence: 99%
“…In contrast, the lack of a systematic approach to relationship management may lessen the benefits of a strategic alliance outside the perimeter of the industrial group in the case of Company Alpha. Second, firms should avoid the adoption of fashionable digital solutions in favour of configurations that actually align with organisation sensemaking (Sanchez-Riofrio et al, 2021). Firm-specific approaches are needed to reflect the non-linear relationship between strategic planning and strategy deployment when digital technologies are involved (Li, 2020).…”
Section: Jmtm 349mentioning
confidence: 99%
“…Furthermore, Sanchez-Riofrio et al (2021) found that firms' adoption of digital technologies (i.e., digitalization) enhances transaction efficiency and improves firm performance. In research work variables in use are return on investment, gross profit, net margin.…”
Section: Measuring Digitalization Impact On Company Performancementioning
confidence: 99%
“…Along with the development of e-commerce, traditional fashion houses are also undergoing digital transformation to ensure their competitiveness [14]. Burberry Group plc's utilization of online channels during the pandemic exemplifies the strategic synergy between digital platforms and resilience.…”
Section: Introductionmentioning
confidence: 99%